Managing english language curriculum reform in Malaysian primary schools issues and challenges / Farah Hussan Sahib and Mahani Stapa - Hussan Sahib, Farah; Stapa, Mahani (2021)
This paper examines the scenery of English language curriculum reform in the Malaysian primary education system. It starts by unveiling the status of English language since Malaysia achieved its independence from the British colony. It provides an overall representation of the alternate government decision positioning English language in the Malaysian education system. It then reviews the initiatives and realities of each English language curriculum reform. In particular, the Integrated Curriculum for Primary School (ICPS) which was launched in 1982, the New Primary School Standards-Based Curriculum for English language education (SBELC), introduced in 2011, and the recent amalgamation of Common European Framework of Languages (CEFR) in Malaysia Education Roadmap (2015-2025) were duly discussed. This paper highlights the impeding factors which led to the inconsistency between the intended national curriculum and actual classroom realities such as language proficiency of teachers, insufficient support and guidance for the teachers to cope with the reforms and centralised education structure. The emerging paradoxical challenges that teachers experienced throughout both language policy and curriculum reforms have aggravated the implementation of the curriculum, which consequently is deemed for immediate attention and to the extent for an additional transformation